A Retrospective Study of Laboratory-Based Enteric Fever Surveillance, Pakistan, 2012–2014. (27th July 2018) - Qamar, Farah Naz; Yousafzai, Mohammad Tahir; Sultana, Shazia; Baig, Attaullah; Shakoor, Sadia; Hirani, Farzeen; Wassay, Abdul; Khushboo, Sehrish; Mehmood, Junaid; Freeman, Alexander; Date, Kashmira; Garrett, Denise
Abstract : 2% of blood cultures performed at Aga Khan University Pakistan was positive for enteric fever during 2012–2014. Resistance to fluoroquinolone >90%, cephalosporin <0.1%, and multidrug resistance 52% ( Salmonella Typhi) and 2% ( Salmonella Paratyphi). Leukopenia, thrombocytopenia, and encephalopathy were common complications among hospitalized cases. Abstract: Introduction: The Surveillance for Enteric Fever in Asia Project (SEAP) is a multisite surveillance study designed to capture morbidity and mortality burden of enteric fever (typhoid and paratyphoid) in Bangladesh, Nepal, and Pakistan. We aim to describe enteric fever disease burden, severity of illness, and antimicrobial resistance trends in Pakistan. Methods: In this retrospective, cross-sectional study, laboratory records of hospitalized patients who received a blood culture in any of 3 Aga Khan University hospitals in Karachi and Hyderabad, Pakistan, from 2012 to 2014 were reviewed. A case was defined as having a positive blood culture for Salmonella Typhi ( S. Typhi) or Salmonella Paratyphi ( S. Paratyphi). Antimicrobial sensitivity patterns were characterized for all S . Typhi and S . Paratyphi isolates. Medical records were available for abstraction (demographics, clinical features, complications) only among hospitalized cases. Results: Of the 133017 blood cultures completed during the study period, 2872 (2%) were positive—1979 (69%) for S. Typhi and 893 (31%) for S. Paratyphi. Fluoroquinolone resistance was present in >90% of both the S. Typhi and the S. Paratyphi isolates; almost none of the isolates were resistant to cephalosporins. Multidrug resistance (resistance to ampicillin, chloramphenicol, and cotrimoxazole) was observed in 1035 (52%) S. Typhi isolates and 14 (2%) S. Paratyphi isolates. Among S . Typhi and S . Paratyphi isolates, 666 (23%) were linked to hospitalized patients with medical records. Of the 537 hospitalized S. Typhi cases, 280 (52%) were aged 5–15 years, 133 (25%) were aged 2–4 years, 114 (21%) were aged >15 years, and 10 (2%) were aged 0–1 years. Among the 129 hospitalized S. Paratyphi cases, 73 (57%) were aged >15 years, 41 (32%) were aged 5–15 years, 13 (10%) were aged 2–4 years, and 2 (2%) were aged 0–1 years. Significant differences in symptomology between S. Typhi and S. Paratyphi cases were observed for nausea/vomiting, diarrhea, loss of appetite, and headache. Leukopenia, thrombocytopenia, and encephalopathy were the most commonly reported complications among enteric fever cases. No deaths were reported. Conclusion: Evidence of high antimicrobial resistance levels and disease severity support the need for continued surveillance and improved diagnostics for typhoid. Further prospective studies on vaccination as a tool for prevention of enteric fever in Pakistan are needed to inform disease intervention strategies.